Investigating the reasons for students' attendance in and absenteeism from lecture classes and educational planning to improve the situation - Sepideh Mokhtari; Sakineh Nikzad; Saeedeh Mokhtari; Siamak Sabour; Sepideh Hosseini (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: This study investigated the reasons for the students' attendance in and absenteeism from lecture classes from the perspective of professors, students, and educational planning to change the unsatisfactory status quo. MATERIALS AND METHODS: The present study was a narrow needs assessment survey which was performed on students (n = 70) of the Faculty of Dentistry, Tehran University of Medical Sciences, in four stages. In the first stage, the opinions of professors and students about the reasons for absenteeism from the lecture classes were collected. In the second stage, the results of the first stage were discussed by an expert panel to find solutions for the problem. The results of the survey were tabulated, summarized, and discussed. In the third stage, online classes were held as one of the solutions and evaluated in the fourth stage. RESULTS: The results showed that various factors, such as professor empowerment, evaluation system, audiovisual equipment of the classes, educational curriculum, and class schedules, are associated with the students' attendance in the classes. Along with these factors, one of the most important reasons for students' absenteeism from classes in recent years might be the generational differences of students. The evaluation of online classes showed that the ratio of the number of students who actively participated in the online classes to the number of students participating in the online classes varied from 30% to 64% (P < 0.05). CONCLUSION: In addition to improving the factors associating students' attendance in classes, online education is a proper solution for reducing absenteeism in lecture classes and increasing students' active participation from the perspective of professors and students.